Prevalence and Exposure Assessment of Aflatoxins Through Black Tea Consumption in the Multan City of Pakistan and the Impact of Tea Making Process on Aflatoxins - Ismail, Amir; Akhtar, Saeed; Riaz, Muhammad; Gong, Yun Yun; Routledge, Michael N.; Naeem, Iqra (Frontiers in Microbiology, 2020)
Aflatoxins are the highly toxic secondary metabolites of certain fungi, being mainly produced by Aspergillus flavus and Aspergillus parasciticus. Aflatoxins are classified as group 1 category carcinogens by the International Agency for Research on Cancer (IARC). A large number of food commodities are reported to be contaminated with aflatoxins. Tea is the world’s second most consumed beverage and the consumption of tea is increasing day by day. Besides being a source of several health promoting substances, tea leaves are also reported to be contaminated with aflatoxins. However, not a single study is reported from Pakistan regarding the level of aflatoxins in commercially available black tea samples. The current study aimed to quantify the level of aflatoxins in commercially available branded and non-branded black tea samples. The estimated daily intake of aflatoxins through branded and non-branded black tea consumption and the health risk assessment based on the margin of exposure (MOE) approach was assessed. Furthermore, the impact of local tea making processes on the concentration of aflatoxins in tea beverage (filtrate) was also investigated.